KEANEKARAGAMAN PLANKTON DI PERAIRAN SUNGAI ASAHAN SUMATERA UTARA (Diversity Plankton in Asahan River North Sumatera) - Hapiz Fahrezi Hsb; Miswar Budi Mulya; Rusdi Leidonald (AQUACOASTMARINE, 2014)
Plankton is aquatic organism that flying and its moves within the water current. Plankton is classified into phytoplankton (classified as plant) and zooplankton (classified as animal). The present of plankton in the water is determined by the physic and chemical condition of the water. Plankton has a limitation to tolerate the environment parameter so, its diversity is different depend on physical and chemical conditions. This research was conducted during April to May of 2013. The sample was taken from four observation stations 4 repetitions. Using Purposive Random Sampling with method. The result of research indicates thast there are 7 class of phytoplankton,they are : Bacillariophyceae, Chlorophyceae, Conjugatophyceae, Coscinodiscophyceae, Cyanophyceae, Eulenophyceae, Ulvophyceae and 12 class of zooplankton, they are : Branchiopoda, Cladocera, Clitellata, Copepoda Crustaceae, Filosia, Gastropoda, Lobosea, Monogonta, Oligotricheae Tubulinea, and Turbellaria The highest total number of plankton is found in station 4 (2043,707 ind/l) and the lowest total number of plankton isfound on station 3 (1519,707 ind/l). The highest diversity index value (H'-) for each station is found onstation 3 (1,206) and the lowest on station 4 (0,929). The Pearson correlation of analysis indicates the current, BOD5, phosphate and nitrate have positive correlation to diversity of plankton while temperature, brightness, DO and pH have negative correlation to diversity of plankton.Keywords : Plankton, Asahan River, Diversity.